2005
DOI: 10.2527/2005.8351167x
|View full text |Cite
|
Sign up to set email alerts
|

The fatty acid composition of muscle fat and subcutaneous adipose tissue of pasture-fed beef heifers: Influence of the duration of grazing

Abstract: Our objective was to determine the effect of the duration of grazing before slaughter on the fatty acid composition of muscle fat and s.c. adipose tissue (SAT) of beef heifers. Sixty crossbred Charolais heifers (n = 15 per treatment) were assigned randomly to one of four dietary treatments: 45 animals (Treatments 1, 2, and 3, respectively) were housed at the beginning of the experiment, and 15 (Treatment 4) were fed at pasture. Two groups of 15 heifers were moved to pasture 40 d (Treatment 2) and 99 d (Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
108
6
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(148 citation statements)
references
References 30 publications
24
108
6
10
Order By: Relevance
“…Even, a short concentrate period of 50 days cancelled the beneficial synthesis of the n-3 FA from pasture grazing. It seems that content of n-3 FA in muscle fat is highly influenced by the type of diet on which animals were fed during the finishing period, in accordance with other studies (Noci et al, 2005).…”
Section: Pufasupporting
confidence: 90%
See 1 more Smart Citation
“…Even, a short concentrate period of 50 days cancelled the beneficial synthesis of the n-3 FA from pasture grazing. It seems that content of n-3 FA in muscle fat is highly influenced by the type of diet on which animals were fed during the finishing period, in accordance with other studies (Noci et al, 2005).…”
Section: Pufasupporting
confidence: 90%
“…Calves fed exclusively on pasture grazing were able to synthesise higher amounts of n-3 PUFA than calves finished on concentrate, in accordance with the results of French et al (2000), Varela et al (2004) and Nuernberg et al (2005). It is widely documented that 18:3 n-3 can serve as a substrate for further desaturation and elongation of PUFA (Noci et al, 2005). Even, a short concentrate period of 50 days cancelled the beneficial synthesis of the n-3 FA from pasture grazing.…”
Section: Pufasupporting
confidence: 83%
“…Schiavon and co-workers 25 showed a similar MUFA content in beef subcutaneous fat, whereas SFA and PUFA were present in higher and lower amount compared to our results. Noci et al 26 have observed low SFA concentration in heifers and MUFA and PUFA with higher values than our samples.…”
Section: Fatty Acid Composition Of By-productsmentioning
confidence: 38%
“…Palmitic acid C16:0 constituted the second major fatty acid detected [20][21][22][23][24][25][26][27][28] , followed by stearic acid C18:0, 10-19 , palmitoleic acid C16:1 cis, [2][3][4][5] , myristic acid C14:0, 2-4 and linoleic acid C18:2 n6, 2-10 . In the storage fat, the saturated fatty acids SFA were present in significantly p 0.05 greater amounts in calf and young bull 46.76 and 47.62…”
Section: Fatty Acid Composition Of By-productsmentioning
confidence: 99%
“…These changes in FAs are related to human-health benefits (Ha et al, 1987;Ochoa et al, 2004), changes in the microbial population (Boeckaert et al, 2006), influences on animal metabolism (Bauman et al, 2011) or to enhancement of the overall performance of offspring, when fed to dams during pregnancy and lactation (Pickard et al, 2008;Or-Rashid et al, 2010). There are known differences between the FA profile of meat of grass fed animals and animals fed silage or concentrate-based diets (Poulson et al, 2004;Noci et al, 2005), but there is little information regarding the FA profile of cattle fed tropical grasses. Lipid profile and concentration in the diet are two factors that can influence the profile of fat in muscle and milk.…”
Section: Introductionmentioning
confidence: 99%